Optimalisasi Penggunaan Kirinyu (Chromolaena odorata) Sebagai Sumber Bahan Organik Dalam Peningkatan Produksi Wortel (Daucus carota) - Murdaningsih Murdaningsih (AGRICA, 2011)
The aim of this study was to understand the benefits of ‘kirinyu’ as a resource of organic matter in the growth and production of carrots and determine the optimum quantities required. The study used a random group design method using K0 (without kirinyu), K1 (kirinyu 5 ton/ha), K2 (kirinyu10 ton/ha), K3 K3 (Kirinyu 15 ton/ha), and K4 (Kirinyu 20 ton/ha). The variables measured in this study were; plant height, the total number of leaves, length of tubers, the diameter of tubers and weight of fresh tubers per plant per plot and per ha. The results of this study indicate that the use of ‘kirinyu’ as a source of organic matter has a definite influence in the plant height in the ages of 4 MST, 8 MST, 10 MST, 12 MST, and total leaves in the ages of 6 MST, 8 MST. Also, it influences the length of tubers, the weight of tubers per plant per plot and per ha. It was determined that optimum growth of carrots; that is plant height (32.51 cm) total leaves (5.78 cm) length of tubers (10.71 cm) was attained with the use of 20 ton/ha weight of fresh tubers per plant (48.19 grams), per plot (7,93 kg) and per ha (21089,29 kg).